(untitled) (Olhar de Professor, 2011)
This article examines how teachers at a public school in the state of Parana deal with Environmental Education in their disciplines, as well as the importance they attach to it. The qualitative research involved eight teachers from different subject areas who work in basic education. The data were collected through questionnaires. After classifying the data it was verified that in general, high school teachers do not carry out projects about Environmental Education. But issues related to the environment are discussed by some teachers in a timely manner, ie, there are no relation to the other topics dealt in class. The main themes discussed are: environmental preservation, solid waste, global warming and the greenhouse effect, and Agenda 21. The main teaching resources used for dealing with these topics are: conducting research, visiting special locations, using videos, images and texts. Teachers also stimulate the production of educational resources made from recyclable materials. Teachers also pointed out the main difficulties / obstacles encountered in working with environmental education in schools; among them we can highlight students´ lack of interest, lack of community support, lack of materials and resources and lack of students’ awareness. In face of this, it is believed that the school could propose alternative ways to contribute to the formation of critical citizens, engaged with everyday problems that can contribute to minimize or solve them. The development of projects, research or the implementation of Agenda 21 are alternatives that the school have to deal with environment themes in an interdisciplinary way.